2014
DOI: 10.1097/fjc.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Basis for the Medicinal Use of Wrightia tinctoria in Hypertension and Dyslipidemia

Abstract: This study was aimed to offer a possible pharmacological basis regarding the remedial utilization of Wrightia tinctoria in hypertension and dyslipidemia in certain South Asian traditional systems of medicine, using in vivo and in vitro assays. The aqueous methanolic extract of W. tinctoria seeds (Wt.Cr) caused a dose-dependent (1-10 mg/kg) decrease in arterial pressure in anesthetized rats. In the right atria of isolated guinea pigs, Wt.Cr equally inhibited force and rate of spontaneous atrial contractions. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The observed cardiac inhibitory effect of the test material(s) might be attenuating cardiac output leading to a decrease in the blood pressure. Our findings are in line with the cardiac inhibitory effect of medicinal plants causing reduction in the cardiac output, thus resulting in decreased blood pressure [15, 43, 5153]. In summary, it appears that nature has composed the opposing mechanisms not allowing the vasodilator effect to cross the desired limit thus overriding excessive drop in blood pressure, which has usually been observed when using standard antihypertensive drugs [45].…”
Section: Discussionsupporting
confidence: 83%
“…The observed cardiac inhibitory effect of the test material(s) might be attenuating cardiac output leading to a decrease in the blood pressure. Our findings are in line with the cardiac inhibitory effect of medicinal plants causing reduction in the cardiac output, thus resulting in decreased blood pressure [15, 43, 5153]. In summary, it appears that nature has composed the opposing mechanisms not allowing the vasodilator effect to cross the desired limit thus overriding excessive drop in blood pressure, which has usually been observed when using standard antihypertensive drugs [45].…”
Section: Discussionsupporting
confidence: 83%
“…Our results also indicate the possibility that the methanol extracts of these plants can inhibit HFD‐induced vascular damage by preventing hyperuricemia and hyperphosphatemia. The previously reported Ca ++ channel blocking activity of VO and WT (Siddiqi et al, ; Siddiqi et al, ) strengthen the case of using these plants for hepatoprotection. We know that increased concentrations of cytosolic Ca ++ contribute towards hepatotoxicity.…”
Section: Resultsmentioning
confidence: 61%
“…In the current studies, we observed that HFD elevates serum concentrations of GGT, AST, and ALT, as shown in Figure 4. In case of the VO study, the normal concentration of GGT, AST, and ALT were 24.9 ± 1.2 units/L, 126 ± 20.7 units/L, and 58.9 ± 9 units/L, respectively, which were significantly elevated to 51.6 ± 1.9 units/L, reported Ca ++ channel blocking activity of VO and WT (Siddiqi et al, 2012;Siddiqi et al, 2014) strengthen the case of using these plants for hepatoprotection. We know that increased concentrations of cytosolic Ca ++ contribute towards hepatotoxicity.…”
Section: Hepatic Protectionmentioning
confidence: 75%
See 2 more Smart Citations